Introducing Optosonographic Surgical Monitoring Into Clinical Practice - Olga V. Surnina (Journal of Global Pharma Technology, 2020)
Materials and methods: In the period from 2010 to 2017 quite a few people were examined, i.e. a ‘comparison’ group of 200 people and an observation group, i.e. 1667 people. The results were as follows. Optosonographic monitoring in 935 patients (56%) revealed surgical thyroid disease, in 732 patients (44%) revealed a surgical pathology of the mammary glands. Among the identified neoplasms, 741 (79%) were benign ones, and 194 (21%) were malignant ones. The number of patients with mammary neoplasms was 732 patients. Of these, 634 were benign ones (87%) and 95 were malignant ones (13%). Results: The sensitivity in the differential diagnosis by optosonographic method of benign thyroid neoplasms is increased from 63% to 95%, malignant neoplasms from 66% to 96%. Reliability increase from 60% to 98% for the diagnosis of benign breast neoplasms, for malignant ones from 37% to 98%. This allows the use of non-invasive optosonographic monitoring to verify the diagnosis.Keywords: Optosonographic method, Implantation, Mammary gland, Thyroid gland.